Report of case of systemic al amyloidosis in a 65-year-old man with chronic diarrhea and hemolacria: Reporte de un caso de amiloidosis sistémica al en un varón de 65 años con diarrea crónica y hemolacria - Peña - Monge, Eloy Manerinc (2024)
The case of a 65-year-old male with chronic diarrhea, periorbital ecchymosis, and hemolacria is described. Laboratory studies, biopsy, and immunohistochemical analysis were performed to confirm the diagnosis. The dependent variable was the confirmed diagnosis of AL amyloidosis, while the independent variables included clinical symptoms and diagnostic test results. Descriptive techniques were used to analyze the clinical and laboratory data. The patient presented with chronic diarrhea unresponsive to conventional treatment, periorbital ecchymosis, and hemolacria. Diagnostic studies revealed amyloid deposits in the tissues. Immunohistochemical analysis confirmed systemic light chain AL amyloidosis. Specific treatment was initiated, partially improving the symptoms and stabilizing the patient's condition. Systemic AL amyloidosis requires a high index of clinical suspicion for timely diagnosis. The combination of diagnostic studies and early treatment can improve the prognosis of these patients.